History of the Portuguese Society of Anesthesiology - Tavares, Jorge (Journal of the Portuguese Society of Anesthesiology, 2015)
The Portuguese Society of Anesthesiology (PSA), one of the pillars upon which itwas the implementation of the specialty in Portugal, was founded in 1955 as asection of the Society of Medical Sciences of Lisbon. Among its objectives, it isstressed the defend of the interests of members and encourage the study of anesthesiologyas well as individual discipline. The trajectory of PSA was made froma set of interventions targeted to his goals. His first board soon find a place in theworld of its European and global counterparts of the specialty, in which participatedon the founding of World Federation of Societies of Anaesthesiologists (WFSA) andestablish partnerships with foreign counterparts. The arrival of trained specialists innational medical career established in 1968 imposed the adoption of new initiativesincluding the organization of national meetings, the first of which in 1977 and thecreation in 1985 of the PSA Journal, periodic publication intended to be the mainvehicle of scientific production of its partners. The participation of SPA in the educationof the Portuguese anesthesiologists whether through their own organizationsor by granting sponsorships constituted its most salient activity throughout these50 years. Since 2003, the PSA has deepened its cooperation with the Medical Collegeof Anesthesiology. Since 2005, the PSA created thematic sections and workinggroups in order to streamline and diversify their interventions